Unofficial Monumentonyms: Towards the Definition of their Onomastic Status - Maria V. Akhmetova (Вопросы ономастики, 2022)
The paper is devoted to unofficial names of monuments and urban sculpture, or unofficial monumentonyms. The author discusses their usage in field interviews, popular media, Internet discussions, excursions, in texts on local history, and in dictionaries. Particular attention is paid to the aspect of variability of these names. The proposed comparative model for describing their “morphology” suggests the invariance of a monument’s subject (that is parodied in an unofficial name) and the changeability of the verbal form of the onym. The metaphoric nature of the discussed type of names makes them similar to the riddles. The author shows that names of this type verge between toponymy and ideonymy, as well as between proper names and urban folklore. Their usage cases in literary texts and colloquial speech do not always allow us to unambiguously qualify them as onomastic or folklore units. Such verbal formulas are often part of evaluative statements and comments about monuments (their subject, position in urban space, etc.), they can be found in jokes (sometimes just stating the fact that a monument is called in a certain way), become objects of an individual or group naming and, finally, they can be used as proper names in the full sense. These names are often used in a limited social milieu or exist for a short time. Their “canonization” is determined by inclusion in local history discourse, by popularization in media, etc.